Social-geographical essence and content of the competitiveness of the region - Diana Gryniuk (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
The current stage of market transformations in Ukraine requires the changing of existing stereotypes and management. Expecting for administrative reform and economic regionalization of the state requires detailed attention to the scientific concept of "competitiveness of the region." Being economical in nature this concept requires social and geographical understanding. The paper traced the content and nature of the economic competitiveness of the region in social and geographical interpretation. Author presents the fragments of research model components of regional competitiveness. The effective influence of socio-geographical laws, patterns, factors and competitive advantages that determine the strategic potential of the region is figured on. The importance of individual studies of functional subsystems, industrial, social, recreation and tourism, natural resources, administrative and management, investment and innovation under the influence of social transformation is noted. Based on scientific generalizations, the author's definition of region competitiveness was suggested. It is defined by the author as an integrated concept that reveals the state, the process and the outcome of the territory as a socio-economic system. The basis of regional competitiveness is the potential of the territory able to function effectively on the basis of competition (social and geographical) advantages. The main goal here should be improvement of the region population quality of life. The work reveals the contribution of individual schools and social geographers’ studies to the development of regional competitiveness. The importance of further development of the theory and methodology of social and geographical research competitiveness of the region is stressed.